A proposal of experimental protocol to assembly scanning. Issue 3 (4th May 2018) - Coves, Pablo; Léon, Jean-Claude; Rohmer, Damien; Marc, Raphael
ABSTRACT: Acquisition of 3D objects using laser scans has become rather common. Most of the time in mechanical engineering, scanning processes are dedicated to standalone components, as part of a reverse engineering pipeline. Though a product, i.e., a set of assembled components, can also be laser scanned, such a scan has no real interest if the objective is to reverse engineer the whole set of assembly components because of the occluded areas generated by components through their contact areas. Indeed, several scans, with some dismounted components, are mandatory to reduce occlusions. Consequently, how many components should be removed? Into which extent is it possible to obtain a good coverage of each component? How many different assembly configurations should be required to obtain enough information? All these meaningful questions can be addressed under the umbrella of the setting of a scanning protocol. This is the proposal described here where a protocol is described and tested that aims at producing the input of a reverse engineering process devoted to CAD assembly reconstruction. GRAPHICAL ABSTRACT: